2019
DOI: 10.1111/evo.13824
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of a soft‐tissue foraging adaptation in African cichlids: Roles for novelty, convergence, and constraint

Abstract: Understanding the origins of biodiversity demands consideration of both extrinsic (e.g., ecological opportunity) and intrinsic (e.g., developmental constraint) factors. Here, we use a combination of phylogenetic and genetic tools to address the origin of novelty in African cichlids. In particular, we focus on an extreme hypertrophied snout that is structurally integrated with the upper jaw. We show that this bizarre trait has evolved independently in at least two distinct and ecologically successful cichlid cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 75 publications
(137 reference statements)
0
18
0
Order By: Relevance
“…Deeper ventricle shapes are typically associated with more active and athletic fish that require greater blood pressure and stroke work (Claireaux et al, 2005). LF therefore appear to develop a more athletic heart, running counter to our initial expectation that LF is a more efficient forager and should therefore expend less overall energy while feeding, compared to TRC (Conith et al, 2019a). Both species are territorial, with males vigorously defending breeding territories (Ribbink et al, 1983), and a recent study examining activity levels across cichlid species found that LF and TRC exhibit high and indistinguishable levels of activity relative to other species (Lloyd et al, 2020).…”
Section: Morphological Variation Among Hybrids Mimics Variation Obsmentioning
confidence: 73%
See 2 more Smart Citations
“…Deeper ventricle shapes are typically associated with more active and athletic fish that require greater blood pressure and stroke work (Claireaux et al, 2005). LF therefore appear to develop a more athletic heart, running counter to our initial expectation that LF is a more efficient forager and should therefore expend less overall energy while feeding, compared to TRC (Conith et al, 2019a). Both species are territorial, with males vigorously defending breeding territories (Ribbink et al, 1983), and a recent study examining activity levels across cichlid species found that LF and TRC exhibit high and indistinguishable levels of activity relative to other species (Lloyd et al, 2020).…”
Section: Morphological Variation Among Hybrids Mimics Variation Obsmentioning
confidence: 73%
“…Recent studies have also demonstrated that patterns of trait covariation can span tissues with vastly different developmental origins (e.g. Martínez-Vargas et al, 2017;Conith et al, 2019a;Yamamoto et al, 2020). Taken together, it appears that patterns of integration can encompass multiple tissue types, even extending beyond structures in close physical proximity, to act as a global mechanism permitting the skull to operate as a single unit.…”
Section: Phenotypic Integration Is Present Within and Between Dispamentioning
confidence: 99%
See 1 more Smart Citation
“…This species exhibits significant habitat and dietary overlap with L. fuelleborni, another algae foraging species from the rocky shallows. L. fuelleborni is arguably one of the most ecologically successful species in the lake, with numerous anatomical adaptations that enable it to dominate this niche [31,[44][45][46]. How then might another species coexist with such a well-adapted forager?…”
Section: Discussionmentioning
confidence: 99%
“…Labeotropheus cichlids is used as a fulcrum, allowing fish to more easily crop algae from rocks 111 versus the bite-and-twist method observed in other cichlid species (Konings 2007;Conith et al 112 2018), and specifically that increased snout depth may help create this mechanical advantage 113 (Conith et al 2019). A similar method may be used during oral shelling to amplify force while 114 removing snails from their shells.…”
mentioning
confidence: 99%